2007
DOI: 10.1308/003588407x160800
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Access Surgery for Total Hip Arthroplasty – Current Beliefs and Activity Profile in The UK

Abstract: INTRODUCTION There is a strong drive from patients, industry and the media to perform total hip arthroplasty (THA) through a minimal access incision. Currently in the UK, the exact definition and uptake of this procedure is not known.PATIENTS AND METHODS A postal questionnaire was sent to all consultant orthopaedic surgeons in the UK registered with the British Orthopaedic Association.RESULTS Of those performing THA, 23% have performed minimal access hip surgery (MAS). Of users, 63% perform less than 20 cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…According to the study type, 485 (74.85%) were cohorts [ 2 , 3 , 8 12 , 14 316 ], 91 (14.04%) were case-series [ 13 , 317 406 ], 49 (7.56%) were case–control studies [ 407 455 ], nine (1.39%) cross-sectional studies [ 456 464 ], eight (1.23%) protocols for registry-based studies [ 465 472 ] and six (0.93%) randomised control trials (RCT) [ 473 478 ]. Three hundred twenty-seven cohort studies were retrospective [ 2 , 8 , 11 , 14 , 17 , 18 , 21 26 , 29 34 , 36 , 38 , 41 , 42 , 44 46 , 54 56 , 64 71 , 83 91 , 106 118 , 123 , 137 146 , 155 190 , 200 217 , 233 266 , 273 , 281 308 , 311 315 , 479 590 ], and 158 were prospective [ 9 , 10 , 12 , 15 , 16 , 19 , 20 , …”
Section: Resultsmentioning
confidence: 99%
“…According to the study type, 485 (74.85%) were cohorts [ 2 , 3 , 8 12 , 14 316 ], 91 (14.04%) were case-series [ 13 , 317 406 ], 49 (7.56%) were case–control studies [ 407 455 ], nine (1.39%) cross-sectional studies [ 456 464 ], eight (1.23%) protocols for registry-based studies [ 465 472 ] and six (0.93%) randomised control trials (RCT) [ 473 478 ]. Three hundred twenty-seven cohort studies were retrospective [ 2 , 8 , 11 , 14 , 17 , 18 , 21 26 , 29 34 , 36 , 38 , 41 , 42 , 44 46 , 54 56 , 64 71 , 83 91 , 106 118 , 123 , 137 146 , 155 190 , 200 217 , 233 266 , 273 , 281 308 , 311 315 , 479 590 ], and 158 were prospective [ 9 , 10 , 12 , 15 , 16 , 19 , 20 , …”
Section: Resultsmentioning
confidence: 99%
“…For example, the United Kingdom National Joint Registry has defined MIS as an incision length of 10 cm or less. 3 Siddiqui et al 4 defined MIS as reduction of the amount of deep dissection and the length of the skin incision. MIS approaches may be broadly classified into two main categories: small-incision and modified deep-dissection approaches.…”
Section: Definitions and Backgroundmentioning
confidence: 99%
“…That study also found that 63% of the orthopaedic surgeons with MIS experience used MIS in fewer than 20 patients per year, and that 62% of those surgeons used the mini-posterior approach. 3 In the second study, 23 an outpatient clinic survey revealed that patients still consider complication rates and implant survival to be more important than length of rehabilitation, length of hospital stay and length of scar, in that order. However, MIS for THA was popular among the patients surveyed, and most indicated they would choose MIS even in the absence of information on complications and outcomes.…”
Section: Subjective Findings From Patient and Surgeon Questionnairesmentioning
confidence: 99%
“…106 Moreover, some surgeons may have been using a progressively shorter incision in standard THR for many years. 107 Indeed, most of the included studies reported using average incision length of around 20 cm or less for the standard incision group. Hence measurable improvements with further shortening of incisions to less than 10 cm might be expected to be relatively small.…”
Section: Assumptions Limitations and Uncertaintiesmentioning
confidence: 99%
“…However, it has been argued by some that reduction in the dissection of soft tissue is more important with the less invasive approaches rather than incision length itself. 107,108 Yet it is not always clear within the included studies whether the deep dissection was sufficiently different between the mini-incision and standard incision groups. Of note, the cadaver study by Mardones and colleagues 109 comparing the two-incision technique with a single miniincision technique reported that the degree of damage to the abductor muscle was actually greater with the two-incision incision technique.…”
Section: Assumptions Limitations and Uncertaintiesmentioning
confidence: 99%